Overexpression of serum HMGB1 and IDO in esophageal squamous cell carcinoma patients: potential clinical auxiliary diagnostic markers and immunotherapeutic targets - Cui, Wenxuan; Niu, Yinghao; Zhang, Xueyuan; Huang, Beixuan; Shang, Xiaoya; Zhao, Wei; Yan, Xi; Mi, Yunqiang (Frontiers in Oncology, 2024)
BackgroundHigh mobility group box 1 (HMGB1) and indoleamino-2, 3-dioxygenase (IDO) participate in the occurrence and development of esophageal squamous cell carcinoma (ESCC), regulate the tumor immune microenvironment, and are closely related to tumor growth and metastasis. However, the regulatory mechanism of serum HMGB1 and IDO has not been clarified and needs further exploration.MethodsBlood samples of 55 ESCC patients initially hospitalized in the Fourth Hospital of Hebei Medical University from August 2021 to January 2022 were selected as the ESCC group, and relevant clinical data were collected, and blood samples from 40 healthy people during the same period were selected as the control group. Serum HMGB1 and IDO levels were determined by ELISA, and lymphocyte subsets in peripheral blood of all subjects were detected by flow cytometry. The correlation between the expression levels of HMGB1 and IDO in ESCC cells was detected by Western blot.ResultsSerum HMGB1 and IDO levels were significantly increased in ESCC patients, and with the progression of ESCC patients, serum HMGB1 and IDO levels were also gradually increased; serum HMGB1 was significantly correlated with IDO; serum HMGB1 and IDO combined with CEA and SCC-Ag were of high value in predicting the clinical progression of ESCC patients; the absolute counts of CD4+CD28+T cells and CD8+CD28+T cells in high HMGB1 group were significantly lower than those in low HMGB1 group, while the percentage of CD4+PD-1+T cells was significantly higher than that in low HMGB1 group; the percentage and absolute counts of CD4+CD28+T cells and the absolute counts of CD8+CD28+T cells in high IDO group were significantly lower than those in the low IDO group, while the percentage of CD8+PD-1+T cells was significantly higher than that in the low IDO group; increased serum HMGB1 and IDO expression levels were closely related to poor prognosis in ESCC patients; and HMGB1 may promote IDO expression by activating NF-κB signaling pathway.ConclusionSerum HMGB1 and IDO have a synergistic effect, they inhibit immune function and promote tumor progression in ESCC patients, and also lead to poor prognosis.